THE EFL TEACHERS’ CONSTRAINTS IN IMPLEMENTING CURRICULUM 2013 - Tandang, Amad P; Ikhsanudin, Ikhsanudin; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe implementation of curriculum 2013 contains complex aspects and a high standard of national education target. Changing elements from curriculum KTSP into curriculum 2013 must be understood, adopted, adapted and manifested in the teaching and learning process by the teachers. The eight Standards of National Education as the guideline for the teachers in implementing curriculum 2013 are obligatory. These standards include (1) Standard of Content, (2) Standard of Graduation Competency, (3) Standard of Process, (4) Standard of Educator and Education Staff, (5) Standard of Facilities, (6) Standard of Management, (7) Standard of Finance, and (8) Standard of Evaluation or Assessment. However, there are constraints faced by English teachers at SMA Negeri 1 Bengkayang in implementing curriculum 2013. A case study was designed to solve this problem. There were three sources of data used in this research, namely documentation of curriculum 2013 of SMA  Negeri 1 Bengkayang, interview and direct-observation toward the implementation of curriculum 2013 in teaching learning activity. The results establish that the common constraints faced by the English teachers were the standard of graduation competency, the standard of evaluation/assessment, the standard of process and the standard of facilities. One of the efforts that can be done in solving these teachers? constraints is by discussing the problems to the principal and the school community based on the constraints that they face. Moreover, the government as the authority responsible for the implementation of the curriculum has to give more training and guidance to the teachers. Keywords: Curriculum 2013, Implementation, EFL Teachers? Constraints